Disciplinary self-reflection in Serbian sociology: findings of an in-depth interview - Vuković, Ana (Sociološki pregled, 2023)
This paper is based on the data from the author’s interviews with our sociologists of different generations and places of employment. In the qualitative research, the following questions, among others, were analyzed: 1. whether sociology is in crisis; 2. theoretical and methodological pluralism in sociology; 3. the sociologist’s potential (sociological approach, sociologist’s imagination) to investigate the problems of contemporary society. Based on the analysis of the answers, the following items were considered: 1. the social position of sociology as a scientific and research discipline; 2. the potential and applicability of sociological knowledge to the problems faced by the sociological profession itself. The author concludes that, according to our sociologists, sociology in Serbia cannot boast of any particular epistemological successes in the field of researching global structures and understanding the world-historical processes in which Serbian society finds itself, but that its potential for research is considerable and that, as a first step, it is necessary for sociology to return to the study of social structure, i.e., society in totality, as its main epistemological task.